2019
DOI: 10.1007/s00216-019-01588-6
|View full text |Cite
|
Sign up to set email alerts
|

In situ analysis and imaging of aromatic amidine at varying ligand densities in solid phase

Abstract: We report the development of a fast and accurate fluorescence-based assay for amidine linked to cellulose membranes and Sepharose gel. The assay is founded on the glyoxal reaction, which involves reaction of amidine group with glyoxal and an aromatic aldehyde, leading to the formation of a fluorophore that can be analyzed and quantified by fluorescence spectroscopy and imaging. While the assay has been reported previously for aromatic amidine estimation in solution phase, here we describe its adaptation and ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In the past, we have modified CA discs chemically and demonstrated their feasibility as a template for fluorometric estimations. 49 The CA microwell plates will similarly form excellent platforms for fluorescence-based assays too. CA is highly amenable to chemical modification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, we have modified CA discs chemically and demonstrated their feasibility as a template for fluorometric estimations. 49 The CA microwell plates will similarly form excellent platforms for fluorescence-based assays too. CA is highly amenable to chemical modification.…”
Section: Discussionmentioning
confidence: 99%
“…26 In previous studies reported by our group, we chemically functionalized commercially available cellulose acetate (CA) discs and demonstrated their efficacy in uorescence-based detection of analytes. 27,28 The growing interest in PADs, coupled to our previous experience in developing chemically derivatized CA discs for analyte detection, has inspired the work being reported in this manuscript. Amidst growing concerns over the staggering amount of plastic waste being generated in scientic laboratories worldwide, 6 and an immediate need to curb the use of single use plasticware, 3 here we report the fabrication of 96-well-format cellulose acetate (CA) plates as viable substitutes for plastic multiwell plates.…”
Section: Introductionmentioning
confidence: 99%